Origem e distribuição das artérias celíaca e mesentérica caudal em aves de corte (Gallus gallus domesticus) da linhagem AP95 - Tosta, Cíntia Roberta Neves (2018)
Brazilian poultry farming is one of the agribusiness sectors that most generates profits for the country. Brazil's leading position, as the second largest producer and largest exporter of chicken meat in the world since 2010, drives several lines of research in this area. The morphological study of the digestive tract is one of them, since it is directly related to feed conversion, carcass yield and weight gain, fundamental characteristics to the profitability of the sector. In the present study the lineage studied was the AP95, are broilers. The thesis was divided in three chapters, the first referring to the importance of poultry farming in Brazil, morphology and irrigation of the digestive tract, subjects discussed in the other chapters. In the second and third chapters, already written in the format for publication, the objective was to describe the origin and distribution of the celiac and mesenteric caudal arteries, respectively. The studies carried out in this work offer a pattern of branching of the main arteries that feed the digestive and nutrient absorption organs in broilers of the AP95 lineage, and may serve as a subsidy to other works, especially descriptive animal morphology.